2014
DOI: 10.1038/mp.2014.88
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione deficit impairs myelin maturation: relevance for white matter integrity in schizophrenia patients

Abstract: Schizophrenia pathophysiology implies both abnormal redox control and dysconnectivity of the prefrontal cortex, partly related to oligodendrocyte and myelin impairments. As oligodendrocytes are highly vulnerable to altered redox state, we investigated the interplay between glutathione and myelin. In control subjects, multimodal brain imaging revealed a positive association between medial prefrontal glutathione levels and both white matter integrity and resting-state functional connectivity along the cingulum b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
103
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(110 citation statements)
references
References 72 publications
5
103
0
2
Order By: Relevance
“…Another recent study reported reduced glutathione only in schizophrenia patients carrying a risk variant of the gene coding for the ratelimiting enzyme in glutathione synthesis [22]. Four other studies reported no statistically significant differences in glutathione levels in the posterior medial frontal cortex [23], mPFC [24] or anterior cingulate cortex (ACC) [25,26]. However, two out of the four found a trend toward reduced glutathione in schizophrenia [24,25] and in one, lowered levels of glutathione were associated with negative symptoms [24].…”
Section: Introductionmentioning
confidence: 95%
“…Another recent study reported reduced glutathione only in schizophrenia patients carrying a risk variant of the gene coding for the ratelimiting enzyme in glutathione synthesis [22]. Four other studies reported no statistically significant differences in glutathione levels in the posterior medial frontal cortex [23], mPFC [24] or anterior cingulate cortex (ACC) [25,26]. However, two out of the four found a trend toward reduced glutathione in schizophrenia [24,25] and in one, lowered levels of glutathione were associated with negative symptoms [24].…”
Section: Introductionmentioning
confidence: 95%
“…112,113 In SZ patients, a direct role for redox control of myelin is seen in the positive correlation between prefrontal GSH levels and functional anisotropy along the cingulum bundle, which connects the ACC to limbic structures. 114 The importance of redox control for white matter integrity and oligodendrocyte development is further supported by animal models and in vitro research. Redox state controls oligodendrocyte maturation as well as the switch between proliferation (reduced state) and differentiation (oxidized state).…”
Section: Oligodendrocyte Sensitivity To Redox Statementioning
confidence: 99%
“…Redox state controls oligodendrocyte maturation as well as the switch between proliferation (reduced state) and differentiation (oxidized state). 114,115 Abnormal redox control would interfere with oligodendrocyte development. Consistent with this, Gclm-KO mice bearing a 70% GSH deficit within brain and increased oxidative stress marks in the PFC and ventral hippocampus 85,87 have lower levels of mature oligodendrocytes and myelin in the peripubertal period 114 (figure 2).…”
Section: Oligodendrocyte Sensitivity To Redox Statementioning
confidence: 99%
See 2 more Smart Citations